(untitled) (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study is to investigate the concept of gum arabic (Acacia senegal (L.) Willd.) as microencapsulation for traditional healthy food modified with the concept of powder drying with that derived from fermented Sumbawa mare’s milk with the concept of improving the integrity of healthy processed food products. Materials and Methods: The use of gum arabic (Acacia senegal (L.) Willd.) as a microencapsulant of Sumbawa mare’s milk powder with treatments (T1: 20%, T2: 24%, T3: 28%, and T4: 32%). Fermented Sumbawa mare’s milk samples were dried using the oven vacuum foam drying method with gum arabic binder at 70°C for 420 min. Evaluation of product test results by analyzing antibacterial, antioxidant, Escherichia coli concentration, protein content, and microstructure. Results: Based on the treatment of the results of the research, it has been significant (p < 0.01) that Sumbawa mare’s milk powder with the use of gum arabic as a microencapsulant known antibacterial test (Lactobacillus casei ATCC 393:4.56 mm, Bacillus subtilis ATCC 6633:7.36 mm, E. coli ATCC 25922:12.25 mm, and Pseudomonas aeruginosa ATCC 15442:12.2 mm), as well as an antioxidant test, which has a value of (46.13 ± 0.73c), microstructure, and protein content using liquid chromatography-mass spectrometry/mass spectrometry analysis, which is reinforced with health pharmaceutical information with literature studies. The E. coli test (food quality test) had a value of 0 CFU/gm, with the results shown in treatment T4 (32%). Conclusion: The use of gum Arabic as a natural additive microencapsulant can be promising in the production of Sumbawa mare’s milk powder. The results obtained have a significant effect on increasing protection and reducing the risk of unwanted pathogenic microbacterial contamination, can reduce antioxidant levels, and provide knowledge for the general public in improving the quality and healthy nutrition of traditional foods. J. Adv. Vet. Anim. Res., 12(2): 610–620, June 2025 http://doi.org/10.5455/javar.2025.l925